2014
DOI: 10.1080/1351847x.2014.948216
|View full text |Cite
|
Sign up to set email alerts
|

A sequential purchasing power parity test for panels of large cross-sections and implications for investors

Abstract: In this paper we use monthly time series data for not less than 64 countries and a new sequential approach to test for purchasing power parity (PPP). The results are strong in that the evidence in favor of PPP is very weak. In fact, for the US-dollar-based exchange rates the evidence is basically non-existent. In order to eliminate the effect of the base currency, we also apply the sequential PPP test to all pairs of exchange rates, and find similarly weak evidence of PPP. However, for those rates where eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The results lead to the conclusion that the long-run PPP hypothesis in China does not hold over the sample period January 1994 to November 2010 [6]. A recent study also found that the evidence in favor of PPP is very weak when using monthly time series data for not less than 64 countries and a new sequential approach to test for PPP [7]. While a study has a mixed result by testing the validity of long-run purchasing power parity for 20 African countries using quarterly data.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The results lead to the conclusion that the long-run PPP hypothesis in China does not hold over the sample period January 1994 to November 2010 [6]. A recent study also found that the evidence in favor of PPP is very weak when using monthly time series data for not less than 64 countries and a new sequential approach to test for PPP [7]. While a study has a mixed result by testing the validity of long-run purchasing power parity for 20 African countries using quarterly data.…”
Section: Literature Reviewmentioning
confidence: 98%